Compound Kushen Injection Protects Skin From Radiation Injury via Regulating Bim - Zheng, Jianxiao; Li, Gong; Wang, Juanjuan; Wang, Shujing; Tang, Qing; Sheng, Honghao; Wu, Wanyin; Wang, Sumei (Frontiers in Pharmacology, 2021)
Background: Radiation-induced skin injury is a major side-effect observed in cancer patients who received radiotherapy. Thus identifying new radioprotective drugs for prevention or treatment of post-irradiation skin injury should be prompted. A large number of clinical studies have confirmed that Compound Kushen injection (CKI) can enhance efficacy and reduce toxicity of radiotherapy. The aim of this study is to confirm the effect of CKI in alleviating radiotherapy injury in the skin and explore the exact mechanism. Methods: 60 patients who met the inclusion/exclusion criteria were allocated to treatment group (CKI before radiotherapy) or control group (normal saline before radiotherapy) randomly. MTT assay, flow cytometry, Western Blot, and transient transfection were performed to detect the cell viability, cell apoptosis and Bim expression after treatment with CKI or/and radiotherapy. Results: CKI had the effect of alleviating skin injury in cancer patients who received radiotherapy in clinic. CKI induced cancer cell apoptosis when combined with irradiation (IR), while it reversed the induction of cell apoptosis by IR in human skin fibroblast (HSF) cells. And Bim, as a tumor suppressor, was induced in cancer cells but had no change in HSF cells when treated with CKI. Moreover, the above effect could be attenuated when Bim was silenced by siRNA. Conclusion: We conclude that CKI represents a promising radio-protective agent with a potential differential beneficial effect on both cancer cells (inducing apoptosis) and HSF cells (providing radio-protection via inhibiting IR-induced apoptosis), via regulating Bim. Our study uncovers a novel mechanism by which CKI inhibits human cancer cell while protects skin from radiotherapy, indicating CKI might be a promising radio-protective drug. Clinical Trial Registration: Chinese Clinical Trial Registry (www.chictr.org.cn), identifier ChiCTR2100049164.